ANALYSIS OF CASSAVA FARMING BUSINESS RISK USING ANALYTIC NETWORK PROCESS - Reza Hanafi Lubis; Dita Deviana Fadhilah; Sriwardany; Wan Dian Safina; Rainal Sunny (CV. Radja Publika, 2024)
It is important to develop research to support food and energy sustainability. This includes managing existing risks, because risk is the core of the paradigm underlying risk management initiatives. This research is aimed at analyzing priority risks in the on-farm aspects of cassava. The research location is in Serdang Bedagai Regency, which is a cassava production center in North Sumatra. This research uses the analytic network process method with the help of superdecision software. We involved three experts in the field of cassava farming who we chose based on experience, knowledge and interests in cassava cultivation in the research area. The identification results in this research found five stages carried out in cassava farming and each stage has potential risks. We also identified three risk criteria and eleven risk sub-criteria. Through analysis using the analytic network process method, we have found that the three priority risks in this research are the risk of low market prices, fertilizer costs and flood risk. Based on the results of this research, we have also explained the managerial implications intended for the future progress of cassava farming.